2020
DOI: 10.29333/ejecs/417
|View full text |Cite
|
Sign up to set email alerts
|

One Size DOES NOT Fit All: Black British-Born Mental Health Nurses and Factors Influencing their ‘National’ Health Service Career Progression

Abstract: Evidence suggests that Black and Minority Ethnic nurses in England’s National Health Service significantly lag behind their White counterparts in Bands 8a, 8b, 8c, 8d & 9 and ‘Very Senior Managers’ positions. Some attribute unequal positions of these nurses to discrimination, racism, exclusion, classism and other forms of disadvantage. Other factors however, are obscured through the accounts of predominantly Black overseas nurses. National Health Service Trusts’ workforce data tends to be gathered using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Subject to the effects of colonialism and gender discrimination, NHS nurses who are female and racialized experience greater disparities in promotions and pay when compared to others ( Milner et al., 2020 ). In an interview study, Isaac (2020) suggested that Black British-born nurses were socialized to employ a defence of their “British cultural capital” (p. 97), comprised of their British identity and positive social contributions, to override systemic racism in the NHS. Although additional theoretical work by critical race scholars is needed in this area, particularly in the contexts of Brexit and the rise of nationalistic populism, the hero discourse may perpetuate the idealization of certain archetypes of nurses based on whiteness and acceptable nationality.…”
Section: Discussionmentioning
confidence: 99%
“…Subject to the effects of colonialism and gender discrimination, NHS nurses who are female and racialized experience greater disparities in promotions and pay when compared to others ( Milner et al., 2020 ). In an interview study, Isaac (2020) suggested that Black British-born nurses were socialized to employ a defence of their “British cultural capital” (p. 97), comprised of their British identity and positive social contributions, to override systemic racism in the NHS. Although additional theoretical work by critical race scholars is needed in this area, particularly in the contexts of Brexit and the rise of nationalistic populism, the hero discourse may perpetuate the idealization of certain archetypes of nurses based on whiteness and acceptable nationality.…”
Section: Discussionmentioning
confidence: 99%
“…The setting of the 16 articles spanned the globe; three were set in the United States of America (USA) (Moyer et al, 2018; Nazareno et al, 2021; Semu, 2020) and South Africa (Dworzanowski‐Venter, 2017; van der Heever et al, 2019; Shung‐King et al, 2018). Two articles were set in the United Kingdom (Isaac, 2020; Qureshi et al, 2020), and one paper had a global focus (Dhatt et al, 2017). The remaining seven articles were set in India (Timmons et al, 2016), Kenya (Muraya et al, 2019), New Zealand (Aspinall et al, 2021), Norway (Drange & Karlsen, 2016), Oman (Hallward & Bekdash Muellers, 2020), Portugal (Santos & Amancio, 2019) and Switzerland (Ammann et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Black and Minority Ethnic (BAME) nurses in England's National Health Service have been shown to significantly lag behind their White counterparts in the higher salary bands and at very senior manager level positions, suggesting discrimination is a hindering factor of career progression. For British born Black nurses, socialisation and internalising what Isaac (2020) described as the cultural capital that comes from being born in Britain helped to override the ‘hindering factor’ of ‘Black ethnic identity’. However, overseas born Black African nurses did not have the same experiences.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations